2021
DOI: 10.1002/ps.6482
|View full text |Cite
|
Sign up to set email alerts
|

Activator protein‐1 mediated CYP6ER1 overexpression in the clothianidin resistance of Nilaparvata lugens (Stål)

Abstract: BACKGROUND Nilaparvata lugens, a destructive rice pest in Asia, has developed resistance to many insecticides, including the neonicotinoid clothianidin. CYP6ER1 plays an important role in N. lugens resistant to clothianidin, but only limited information on the transcriptional regulation of CYP6ER1 overexpression in clothianidin resistance is available. RESULTS In this study, the transcription factor activator protein 1 (AP‐1) was found to be overexpressed in a clothianidin‐resistant strain of N. lugens and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
(45 reference statements)
2
16
0
Order By: Relevance
“…For instance, transcription factors CncC/Maf, CREB, HNF4 and AhR/ARNT has been respectively proved to participate in the regulation of P450 genes mediating imidacloprid susceptibility in insects (Cheng et al, 2021;Kalsi and Palli, 2017;Wang et al, 2021;Yang et al, 2020). AP-1 protein was showed to mediate clothianidin resistance by regulating CYP6ER1 in N. lugens (Jin et al, 2021). In the present study, it was found that FoxO mediated nitenpyram resistance in N. lugens, which might be through regulating CYP4CE1 expression by FoxO.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…For instance, transcription factors CncC/Maf, CREB, HNF4 and AhR/ARNT has been respectively proved to participate in the regulation of P450 genes mediating imidacloprid susceptibility in insects (Cheng et al, 2021;Kalsi and Palli, 2017;Wang et al, 2021;Yang et al, 2020). AP-1 protein was showed to mediate clothianidin resistance by regulating CYP6ER1 in N. lugens (Jin et al, 2021). In the present study, it was found that FoxO mediated nitenpyram resistance in N. lugens, which might be through regulating CYP4CE1 expression by FoxO.…”
Section: Discussionsupporting
confidence: 50%
“…In N. lugens, AKH-mediated ROS burst induced CYP6ER1 expression by activating CncC and MafK after imidacloprid exposure (Tang et al, 2020). Additionally, activator protein 1 (AP-1) was found to be overexpressed in a clothianidin resistant strain and eld resistant populations of N. lugens, regulating the expression of CYP6ER1 to mediate clothianidin resistance (Jin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to note that, while the data presented in the current work provide valuable information on deregulated transcripts in response to insecticides in L. decemlineata not previously exposed to various compounds, subsequent efforts are warranted to better delineate the underlying roles, if any, of these targets in the process of insecticide resistance. Characterizing the expression status of these transcripts in L. decemlineata populations with confirmed resistance towards a given compound of interest such as clothianidin, similar to work conducted on the potential role of CYP6er1 in clothianidin-resistant populations of N. lugens [ 39 ], would be an interesting starting point to better position these targets within the context of insecticide resistance in this potato pest. It is finally important to point out that leveraging, in the mid- to long-term, a high-throughput sequencing analysis approach to decipher a plethora of deregulated transcripts, besides the select group assessed in the current work, would yield valuable information and should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…42 For example, clothianidin treatment enhanced the expression of CYP6ER1in N. lugens through the transcription factor activator protein 1 (NlAP-1). 43 In Bemisia tabaci, the upregulation of CYP6CM1 by imidacloprid was through the mitogen-activated protein kinase (MAPK)-directed activator transcription factor CREB (cAMP-response element binding protein). 44 So, we supposed that the effects of flonicamid treatment on salivary protein gene expressions were through some important transcription factors, which need further identification and verification in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For example, clothianidin treatment enhanced the expression of CYP6ER1 in N. lugens through the transcription factor activator protein 1 ( NlAP-1 ) . In Bemisia tabaci, the upregulation of CYP6CM1 by imidacloprid was through the mitogen-activated protein kinase (MAPK)-directed activator transcription factor CREB (cAMP-response element binding protein) .…”
Section: Discussionmentioning
confidence: 99%